Design of higher gain 1×4 cylindrical dielectric resonator antenna for mm-wave base stations - El Hasnaoui, Yassine; Mazri, Tomader (Bulletin of Electrical Engineering and Informatics, 2024)
In this work, a cylindrical-shaped dielectric resonator antenna (DRA) with four elements is designed and presented at 28 GHz for millimeter-wave applications. The microstrip line is designed to excite the dielectric resonator (DR) with a relative permittivity of 8.3, and then the proposed single cylindrical DR antenna has been mounted on a FR4-Epoxy substrate with a relative permittivity of 4.4 and a thickness of 1.8 mm. However, the optimized single element was used to create a particular array for improving the gain and achieving the required antenna performance. The resulting antenna enabled a response range for the reflection coefficient from 26.8 GHz to 30.6 GHz, which covers the operational frequency. This allows for a maximum gain of 19.07 dB, an impedance bandwidth of 3.8 GHz, and a total efficiency of 80.62%, meeting the requirements for millimeter-wave and fifth-generation applications.